The Effect of ICT on CO2 Emissions in the GCC Countries: Does Globalization Matter? - Ebaidalla, Ebaidalla Mahjoub; Abusin, Sana (International Journal of Energy Economics and Policy, 2022)
Despite the significant impact of information and communication technologies (ICTs) on environment, whether globalization enhances the role of ICT in environmental quality is a question that received limited research attention. This paper examines the impact of ICTs on carbon dioxide (CO2) emissions in the presence of globalization in the Gulf Cooperation Council (GCC) countries for the period of 1995-2018. The study adopted the mean group (MG) and augmented mean group (AMG) estimation methods to address the problems of cross-sectional dependence and heterogeneity. Unexpectedly, the results of both MG and AMG revealed that the spread of ICT exerts positive and significant impact on CO2 emissions, implying that ICTs worsening the environment in GCC countries. However, the adverse impact of ICTs on CO2 emissions can be mitigated through globalization process. Therefore, policy makers in GCC countries should utilize globalization process, adopting advanced energy-saving technologies that reduce energy consumption and improve environmental quality.